Packaging bag for functional food as well as preparation method and fresh-keeping process of packaging bag

By adopting a multi-layer structure in the packaging bag, including a matte layer, a water barrier layer and a transmissive layer, effectively blocking light, water vapor and oxygen, the existing packaging has solved the problem of insufficient moisture-proof, oxygen barrier and light-shielding capabilities, and achieved better food shelf life and nutrient preservation effect.

CN119898100APending Publication Date: 2025-04-29SHANDONG SHENGHAI HEALTH PROD CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510410363.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing aluminum-plastic film packaging has shortcomings in moisture-proof performance, oxygen barrier ability and light-shading ability, which leads to problems such as moisture absorption, fading appearance, deterioration of taste and nutrient loss during storage of functional foods.

Method used

The packaging bag consisting of a matting layer, a water barrier layer, a water barrier layer, a drying layer and a heat sealing layer are adopted, and a matting layer made of polyamide, a matting agent, a coupling agent and an antioxidant, a water barrier layer made of a cross-linked composite structure of polyvinyl alcohol masterbatch and aluminum filler, and a water barrier layer made of ethylene and chloroethylene copolymer films are effectively blocked light, water vapor and oxygen, and reduced oxidation and moisture absorption of food.

Benefits of technology

It significantly improves the barrier performance of packaging bags, extends the shelf life of food, maintains the taste and flavor of the product, and effectively prevents the loss of nutrients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898100A_ABST
    Figure CN119898100A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging parts, and particularly relates to a packaging bag for functional food and a preparation method and a freshness locking technology of the packaging bag. The packaging bag for the functional food comprises a matting layer, a water blocking layer, a permeation blocking layer, a drying layer and a heat sealing layer, wherein the matting layer, the water blocking layer, the permeation blocking layer, the drying layer and the heat sealing layer are sequentially connected from top to bottom; the matting layer is prepared from polyamide, a matting agent, a coupling agent and an antioxidant, the water blocking layer is prepared from polyvinyl alcohol master batches, filler and a slipping agent, the permeation blocking layer is an ethylene and chlorotrifluoroethylene copolymer film, the drying layer is a silica gel desiccant layer, and the heat sealing layer is prepared from high-density polyethylene. The barrier property is good, the taste and flavor of the product can be better reserved, and nutrient loss is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of packaging, and in particular relates to a packaging bag for functional food, a preparation method thereof and a freshness-locking process. Background Art

[0002] Aluminum-plastic film is light in weight, thin in thickness, and flexible in appearance design. It has the characteristics of waterproof, barrier, decorative and easy to carry. It is generally divided into three layers, namely water barrier layer, barrier layer and heat seal layer. Aluminum-plastic film is widely favored in the field of health food. However, during the use of aluminum-plastic film, there are still problems such as weak moisture resistance, poor oxygen barrier ability, and insufficient light shielding ability, which leads to moisture absorption, fading appearance, gradual deterioration of taste, and serious loss of nutrients as the shelf life of food increases.

[0003] Functional foods such as vitamin C, also known as ascorbic acid, play an important physiological role in the body: scavenging free radicals, improving the body's immunity, promoting collagen synthesis and repair, maintaining the normal structure and function of skin, blood vessels, bones and other tissues, promoting the absorption and utilization of iron, and preventing iron deficiency anemia. Vitamin C is a compound that is easily oxidized under oxygen and light conditions. After oxidation, it will be converted into dehydroascorbic acid and dihydroascorbic acid with greatly weakened antioxidant effects and 2,3-ketoascorbic acid with almost no antioxidant effect; the production of these oxidation products will further accelerate the destruction and attenuation of ascorbic acid. Once vitamin C is oxidized, its antioxidant capacity and bioavailability in the body are greatly reduced. Therefore, vitamin C products need to be packaged to prevent them from oxidizing and deteriorating.

[0004] Aluminum foil bags are often packed with inert gas to replace the oxygen in the package or vacuum to preserve food. This method cannot avoid adverse changes in the product components caused by water vapor and oxygen during the production process, nor can it prevent oxygen and water vapor outside the package from entering the packaging bag after packaging.

[0005] Chinese patent CN111688315A discloses a thermochromic plastic packaging film, including an outer film layer, a reinforcing film layer, a barrier film layer and an inner film layer; the outer film layer includes a matte film and a printing layer, the matte film has a thickness of 20-30 μm, and the printing layer has a thickness of 2-5 μm; the reinforcing film layer is provided with thermochromic microcapsules, and the thickness of the reinforcing film is 60-90 μm; the barrier film layer is an aluminized film or aluminum foil, and the thickness of the barrier layer is 7-15 μm; the inner film layer includes a cast polypropylene film and a polylactic acid film, and the polylactic acid film is coated with a smooth surface layer on the contact surface with the content. Although the packaging film has a good color change effect, the barrier performance is poor. Summary of the invention

[0006] The purpose of the present invention is to provide a packaging bag for functional food, which has good barrier properties, can better retain the taste and flavor of the product, and effectively prevent the loss of nutrients; the present invention also provides a preparation method and a freshness-locking process for the packaging bag for functional food.

[0007] The packaging bag for functional food of the present invention comprises a matt layer, a water-blocking layer, a permeability-barrier layer, a drying layer and a heat-sealing layer, wherein the matt layer, the water-blocking layer, the permeability-barrier layer, the drying layer and the heat-sealing layer are sequentially connected from top to bottom; the matt layer is made of polyamide, a matt agent, a coupling agent and an antioxidant, the water-blocking layer is made of a polyvinyl alcohol masterbatch, a filler and a lubricant, the permeability-barrier layer is a film of a copolymer of ethylene and chlorotrifluoroethylene, the drying layer is a silica gel desiccant layer, and the heat-sealing layer is made of high-density polyethylene.

[0008] The matting agent is poly-4-methyl-1-pentene and polycarbonate fiber, the coupling agent is vinyl triethoxysilane and vinyl tri(β-methoxyethoxy) silane, and the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 2,6-di-tert-butyl-p-cresol.

[0009] The preparation method of polyethylene masterbatch is as follows: polyethylene, polyethylene glycol, lauric acid, mica, polyvinyl alcohol, quaternary ammonium salt and triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate are put into a mixer, stirred and mixed for 15-20 minutes at a temperature of 35°C and a rotation speed of 400-600r / min to obtain a mixture, and the mixture is sent to a twin-screw extruder, and the twin-screw extruder is divided into nine temperature zones, which are 170°C, 180°C, 200°C, 210°C, 210°C, 215°C, 215°C, 210°C, 205°C, and the screw speed is 160- 200r / min, the mixed material is heated and melted into a melt, and flows out from the die under the push of the screw. After the melt flows out of the die, it is hot-cut into 3×3mm cylindrical particles by a cutter, and cooled by a wind tube to obtain a polyethylene masterbatch; wherein, by weight, polyethylene 80-110 parts, polyethylene glycol 1.0-1.8 parts, lauric acid 0.5-0.8 parts, mica 8-12 parts, polyvinyl alcohol 3-6 parts, quaternary ammonium salt 0.7-1.6 parts and triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate 0.2-1.2 parts; the quaternary ammonium salt is chitosan quaternary ammonium salt.

[0010] The filler is aluminum, and the weight ratio of the polyvinyl alcohol masterbatch to the filler is 94.5-96:3.5-5.5; the lubricant is oleic acid amide, and the weight ratio of the polyvinyl alcohol masterbatch to the lubricant is 94.5-96:2.5-7.

[0011] The preparation method of the dry layer is to mix silicon dioxide and water in a mass ratio of 1:4-6 to form a uniform silica paste, and evenly apply the silica paste on the template with a coating thickness of 0.1-0.3 mm. After coating, use an oven to dry and cure at 95-100°C for 0.5-1 hour to obtain a dry layer.

[0012] The heat sealing layer is made of high-density polyethylene under the conditions of heat sealing pressure 1.5-2.0kg / cm², heat sealing temperature 118-122℃, and tensile strength ≥20MPa.

[0013] The method for preparing a packaging bag for functional food according to the present invention comprises the following steps: (1) Preparation of matt layer The polyamide, matting agent, coupling agent and antioxidant are mixed evenly and added into a twin-screw extruder for melt blending, extrusion, chilling casting, biaxial stretching, washing, drying and cutting to obtain a matting layer; (2) Preparation of water-blocking layer: The polyvinyl alcohol masterbatch is mixed with the filler to obtain a mixed material; the mixed material and the lubricant are added into a conical twin-screw roller extruder and extruded to obtain a water-blocking layer; (3) Preparation of barrier layer: Add a surfactant, an initiator, ethylene and chlorotrifluoroethylene into deoxygenated deionized water, stir and react to obtain a copolymer solution of chlorotrifluoroethylene and ethylene, add a diluent into the copolymer solution of chlorotrifluoroethylene and ethylene to form a homogeneous solution, pour the homogeneous solution onto a glass plate, add an extractant into the homogeneous solution to remove the extractant, and obtain a polymer solution, and cast the polymer solution into a film, i.e., a barrier layer; (4) A layer of solvent-based adhesive is coated on the matte layer, the water-blocking layer and the barrier layer respectively, and the matte layer, the water-blocking layer and the barrier layer are laminated and dried, and then a drying layer is added for hot pressing and lamination, and then a heat sealing layer is flatly attached, extruded after heating, and inflated with compressed air to obtain a packaging bag for functional food.

[0014] In step (1), the melt blending temperature is 240-350°C, the extrusion temperature is 180-230°C, and the chilled casting temperature is 25-35°C.

[0015] The preparation of the matt layer in step (1) comprises the following specific steps: 75-82 parts of polyamide, 5-15 parts of poly-4-methyl-1-pentene, 4-7 parts of polycarbonate fiber, 0.5-1.5 parts of vinyl triethoxysilane, 0.2-0.9 parts of vinyl tri(β-methoxyethoxy)silane, 0.5-2 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.2-1 parts of 2,6-di-tert-butyl-p-cresol are fully mixed and fully melted and blended at 240-350°C through a twin-screw extruder, extruded at 180-230°C, the melt is extruded into a thick sheet, chilled and cast at 25-35°C, and then longitudinally stretched 4-6 times at 125-146°C and transversely stretched 7.5-8.5 times at 150-178°C, the film is cleaned and dried after biaxial stretching, and cut to form a matte layer.

[0016] In step (2), the mixing temperature is 3-12° C. and the mixing time is 15-25 min.

[0017] In step (2), the extrusion is carried out by segmented temperature control, with the temperature of the melting section being set at 65-85°C, the temperature of the final melting homogenization section being set at 90-95°C, the temperature of the homogenization dispersion section being set at 95-100°C, and the temperature of the dispersion section being set at 105-115°C.

[0018] In step (2), the polymer masterbatch is first blended with aluminum at low temperature to improve the dispersion of the inorganic filler in the polymer and avoid the problem of uneven mixing of aluminum and the polymer due to excessive viscosity of the polymer under high temperature conditions.

[0019] In step (3), the surfactant is one or both of fatty alcohol polyoxyethylene ether or polyoxypropylene ether phosphate, the initiator is an ammonium persulfate solution with a mass concentration of 10-15%, the stirring reaction temperature is 55-105°C, the stirring reaction time is 4.5-8 hours, the diluent is one of dimethyl phthalate, diethyl phthalate, diethyl sebacate, tricresyl phosphate or benzophenone, the mixing temperature is 175-235°C, the extractant is one of methanol, ethanol, propanol, n-butanol or ethylene glycol, the removal temperature is 30-50°C, and the mass ratio of deoxygenated deionized water, surfactant, initiator, ethylene, chlorotrifluoroethylene, diluent and extractant is 55-70: 0.12-1.25: 0.08-0.6: 15-28: 0.8-1.2: 25-53: 15-37.

[0020] In step (4), the solvent-based adhesive is ethylene-vinyl acetate copolymer; the hot pressing compounding temperature is 100-200°C, the hot pressing compounding pressure is 0.16-0.41 MPa, and the heating temperature is 195-210°C.

[0021] The freshness-locking process for the packaging bag for functional food according to the present invention is that the raw materials of the functional food are pre-treated and weighed, and then the raw materials are transported to a mixer through a closed pipeline filled with inert gas for uniform mixing, and the uniformly mixed raw materials are transported to a tableting process through a closed pipeline filled with inert gas, and tablets are pressed under completely closed conditions filled with inert gas, and the tablets obtained after tableting are transported to a packaging process through a closed pipeline filled with inert gas, and in the packaging process, tablets are first added to the packaging bag for functional food and then filled with inert gas, and finally the packaging bag is heat-sealed to obtain a functional food product; wherein, the pre-treatment is a treatment through a 20-80 mesh screen, the inert gas is carbon dioxide or nitrogen, the purity of the nitrogen is 99.999%, and the mixing time is 20-40 minutes.

[0022] The freshness-locking process for packaging bags for functional foods according to the present invention is that the raw materials of the functional foods are pre-treated and weighed, the raw materials used for granulation in the raw materials are transported to the granulation process through a closed pipeline filled with inert gas for granulation, the obtained granules are transported to the drying process through a closed pipeline filled with inert gas for drying, the dried granules and the remaining raw materials are transported to a mixer through a closed pipeline filled with inert gas for uniform mixing, the uniformly mixed materials are transported to the tableting process through a closed pipeline filled with inert gas, and the tableting process is carried out after the inert gas is filled. The tablets are compressed under completely closed conditions with an inert gas, and the tablets obtained after compression are transported to the packaging process through a closed pipe filled with inert gas. In the packaging process, tablets are first added to the packaging bag for functional food and then filled with inert gas, and finally the packaging bag is heat-sealed to obtain a functional food product; wherein, the pretreatment is sieve treatment with a 20-80 mesh, the inert gas is carbon dioxide or nitrogen, the purity of nitrogen is 99.999%, the drying temperature is 30-80°C, the drying time is 20-60min, and the mixing time is 20-40min.

[0023] Functional foods include but are not limited to the following products: chewable vitamin C tablets, vitamin C effervescent tablets, multiple B vitamin tablets, multiple mineral tablets, multiple vitamin mineral tablets, pressed candies and other products.

[0024] The present invention adopts inert gas protection and oxygen-isolated closed material transportation in process technology to reduce the contact of materials with light, oxygen and water vapor during the production process.

[0025] After the inert gas protection is adopted in the present invention, the sensory organs and functional components of the products produced during the shelf life are not significantly changed compared with those when the products are just off the production line; the sensory organs and functional components of the products produced without inert gas protection during the shelf life are significantly deteriorated compared with those when the products are just off the production line.

[0026] The present invention adopts an oxygen-isolated and sealed material transportation method to reduce direct contact between the material and oxygen, thereby avoiding the problem of redox reaction between the effective components and oxygen causing attenuation of the effective components.

[0027] Poly-4-methyl-1-pentene and polyamide (PA) in the extinction layer form a refractive index difference, forming a micron-scale concave-convex structure on the surface of the film. The two work together to achieve the extinction effect through multiple light scattering.

[0028] Polycarbonate fibers are embedded in the PA matrix to form an interpenetrating network structure with long-chain poly-4-methyl-1-pentene; the vinyl groups in the coupling agent (vinyl silanes) are bonded to the amide groups of PA and the ester groups of polycarbonate fibers through hydrogen bonds to form a "PA-coupling agent-matting agent" chemical bridge, which reduces interface defects and further improves stability.

[0029] The strong electronegativity of the F atom in the chlorotrifluoroethylene (CTFE) unit in the ethylene-chlorotrifluoroethylene copolymer causes dipole-dipole interactions to form between the molecular chains, increasing the stacking density of the chain segments and effectively reducing the oxygen permeability; at this time, the ethylene unit is inserted into the fluorine chain, destroying the rigid crystalline region of CTFE and forming a "fluorine-carbon alternating" micro-region structure, which can effectively balance barrier properties and flexibility.

[0030] The micron-level surface roughness of the matt layer can disperse the water vapor permeation path, prevent water molecules from forming a continuous liquid film on the surface of the water barrier layer, and reduce the risk of local penetration. The aluminum filler of the water barrier layer is combined with the polyamide matrix of the matt layer through hydrogen bonds and van der Waals forces to form a dual effect of "physical barrier + surface hydrophobicity", further reducing the water vapor transmission rate.

[0031] The matte layer and the drying layer of the present invention can better block light and water vapor in the storage environment from entering the packaging bag and directly contacting the product, thereby minimizing the occurrence of photooxidation reactions of the components in the product and other reactions caused by moisture absorption of the product and the growth of microorganisms, thereby ensuring the quality of the product just off the production line to the greatest extent.

[0032] The function of the extinction layer in the present invention is to block the light source and reduce the destruction of nutrients in food caused by photo-oxidation reaction.

[0033] The water-blocking layer and the drying layer in the present invention can double-block water vapor, thereby preventing the occurrence of other reactions caused by moisture absorption and the breeding of microorganisms in the product.

[0034] The function of the barrier layer in the present invention is to block oxygen and reduce the nutrient destruction caused by the redox reaction between food and oxygen.

[0035] The presence of water vapor will accelerate the occurrence of photo-oxidation and oxygen redox reactions, and light sources will also accelerate the occurrence of aerobic redox reactions. Therefore, under the condition that light, oxygen and water vapor exist at the same time, the three factors will interact with each other, accelerate the negative change of product quality, and make its sensory organs, nutritional components and other aspects gradually deteriorate with time during the shelf life; the matte layer, water-blocking layer, drying layer and barrier layer in the present invention can effectively block light, water vapor and air from entering the packaging bag, and block the favorable factors of photo-oxidation and aerobic redox reactions as much as possible, thereby reducing the occurrence of corresponding destructive reactions.

[0036] The beneficial effects of the present invention are as follows: The surface of the matt layer made of polyamide, matting agent, coupling agent and antioxidant in the present invention presents a microcavity concave-convex structure, which increases the diffuse reflection and scattering of the incident light on its surface, and at the same time, part of the light can be absorbed by its microstructure, thereby reducing the amount of transmitted light to achieve the matt effect. The cross-linked composite structure of the polyvinyl alcohol masterbatch and the aluminum filler in the water-blocking layer can effectively form a waterproof barrier and reduce water vapor penetration. The dry layer can effectively absorb water vapor that passes through the cross-linked composite structure of the polyvinyl alcohol masterbatch and the aluminum filler, and the dual effects play a water-blocking effect. Ethylene and chlorotrifluoroethylene form an alternating copolymer structure in the barrier layer, and the fluorine atoms in the molecular chain are adjacent to the hydrogen atoms of the adjacent molecular chain. The structure is compact and has extremely low permeability to oxygen, water vapor, etc.

[0037] In the process of compounding each layer of the present invention, a solvent-based adhesive cross-linked copolymer group is further introduced to enhance the interaction between molecular chains, reduce the formation of interchain gaps, and increase the difficulty of gas penetration by reducing the path of gas molecules passing through the packaging bag, thereby achieving a barrier effect. The poly-4-methyl-1-pentene in the matte layer, the polyvinyl alcohol masterbatch in the water-blocking layer, and the ethylene and trifluorochloroethylene copolymer in the barrier layer form an overall network cross-linking system through the final composite extrusion, which can greatly improve the barrier performance; in addition, through the arrangement and combination of different materials in each layer, the cross-dislocation of the micropores between the layers can further reduce the diameter of the micropores inside the packaging bag, reduce the penetration path of gas molecules and light, and synergistically improve the overall barrier performance of the packaging bag.

[0038] The invention can better preserve the taste and flavor of the product and effectively prevent the loss of nutrients. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a diagram showing the appearance changes of the products of Example 1 and Comparative Examples 1-4.

[0040] Figure 2 It is a graph showing changes in moisture index of the products of Example 1 and Comparative Examples 1-4.

[0041] Figure 3 It is a graph showing the changes in vitamin C content of the products of Example 1 and Comparative Examples 1-4.

[0042] Figure 4 It is a graph showing changes in nitrogen content in product packaging bags of Example 1 and Comparative Examples 1-4.

[0043] Figure 5 It is a graph showing the changes in moisture index of the products at various stages during the shelf life of Example 1 and Comparative Examples 1-4.

[0044] Figure 6 It is a graph showing changes in vitamin C content index of the products of Example 1 and Comparative Examples 1-4 at various stages during their shelf life.

[0045] Figure 7 It is a graph showing changes in nitrogen content in product packaging bags at various stages during the shelf life of Example 1 and Comparative Examples 1-4.

[0046] Figure 8 This is a graph of the survival rate of L929 cells after treatment with different concentrations of H2O2.

[0047] Fig. 9 It is a graph of the survival rate of L929 cells after treatment with 200mM H2O2 and the products stored for 24 months.

[0048] Fig.10 This is the laser confocal microscopy result of the cells after the product was stored for 24 months.

[0049] Fig.11 It is a diagram showing the appearance changes of the products of Example 2 and Comparative Examples 5-8.

[0050] Fig.12 It is a diagram showing the appearance changes of the products of Example 3 and Comparative Examples 9-12. DETAILED DESCRIPTION

[0051] The present invention is further described below with reference to the embodiments.

[0052] Example 1 The packaging bag for functional food comprises a matt layer, a water-blocking layer, a permeability-barrier layer, a drying layer and a heat-sealing layer, which are connected in sequence from top to bottom; the matt layer is made of polyamide, a matting agent, a coupling agent and an antioxidant, the water-blocking layer is made of a polyvinyl alcohol masterbatch, a filler and a lubricant, the permeability-barrier layer is a film of a copolymer of ethylene and chlorotrifluoroethylene, the drying layer is a silica gel desiccant layer, and the heat-sealing layer is made of a high-density polyethylene.

[0053] The matting agent is poly-4-methyl-1-pentene and polycarbonate fiber, the coupling agent is vinyl triethoxysilane and vinyl tri(β-methoxyethoxy) silane, and the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 2,6-di-tert-butyl-p-cresol.

[0054] The preparation method of polyethylene masterbatch is as follows: polyethylene, polyethylene glycol, lauric acid, mica, polyvinyl alcohol, quaternary ammonium salt and triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate are put into a mixer, stirred and mixed for 15 minutes at a temperature of 35°C and a rotation speed of 500r / min to obtain a mixture, and the mixture is sent to a twin-screw extruder, and the twin-screw extruder is divided into nine temperature zones, which are 170°C, 180°C, 200°C, 210°C, 210°C, 215°C, 215°C, 210°C, 205°C, respectively. , the screw speed is 200r / min, the mixed material is heated and melted into a melt, and flows out from the die under the push of the screw. After the melt flows out of the die, it is hot-cut into 3×3mm cylindrical particles by a cutter, and cooled by a wind tube to obtain a polyethylene masterbatch; wherein, by weight fraction, 90 parts of polyethylene, 1.5 parts of polyethylene glycol, 0.5 parts of lauric acid, 12 parts of mica, 3 parts of polyvinyl alcohol, 1.6 parts of quaternary ammonium salt and 0.8 parts of triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate; the quaternary ammonium salt is chitosan quaternary ammonium salt.

[0055] The filler is aluminum and the lubricant is oleamide.

[0056] The preparation method of the dry layer is to mix silicon dioxide and water in a mass ratio of 1:5 to form a uniform silica paste, and evenly apply the silica paste on the template with a coating thickness controlled at 0.1-0.3mm. After coating, use an oven to dry and cure at 100°C for 0.5 hours to obtain a dry layer.

[0057] The heat sealing layer is made of high-density polyethylene under the conditions of heat sealing pressure 2.0kg / cm², heat sealing temperature 120℃, and tensile strength ≥20MPa.

[0058] A method for preparing a packaging bag for functional food comprises the following steps: (1) Matting layer preparation method 75 parts of polyamide, 5 parts of poly-4-methyl-1-pentene, 5 parts of polycarbonate fiber, 0.6 parts of vinyl triethoxysilane, 0.2 parts of vinyl tri(β-methoxyethoxy)silane, 0.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.2 parts of 2,6-di-tert-butyl-p-cresol are fully mixed and fully melted and blended at 350° C. through a twin-screw extruder, extruded at 180° C., the melt is extruded into a thick sheet, and a sheet is cast at 25° C., and then longitudinally stretched 5 times at 125° C. and transversely stretched 7.5 times at 150° C., and the film is washed and dried after biaxial stretching, and cut to form a matte layer; (2) Preparation method of water-blocking layer: The polyvinyl alcohol masterbatch and the aluminum filler are mixed at a weight ratio of 95:5 in a closed mixing tank at 8°C for 15 minutes to obtain a mixed material; the mixed material and oleic acid amide are added into a conical twin-screw roller extruder for extrusion, and the weight ratio of the polyvinyl alcohol masterbatch to the oleic acid amide is 95:5 to obtain a water-blocking layer; wherein the extrusion is extruded in a segmented temperature control manner, the melting section temperature is set to 70±2°C, the final melting homogenization section temperature is set to 92±2°C, the homogenization dispersion section temperature is set to 97±2°C, and the dispersion section temperature is set to 110±2°C; (3) Preparation method of barrier layer: 0.12 parts of fatty alcohol polyoxyethylene ether, 0.08 parts of ammonium persulfate solution with a mass concentration of 10%, 22.4 parts of ethylene and 1.2 parts of trifluorochloroethylene were added to 55 parts of deoxygenated deionized water, and the mixture was stirred and reacted at 55° C. for 4.5 hours to obtain a trifluorochloroethylene and ethylene (ECTFE) copolymer solution. 25 parts of diluent diethyl sebacate were added to the trifluorochloroethylene and ethylene copolymer solution, and the mixture was mixed at 175° C. to form a homogeneous solution. The homogeneous solution was poured on a glass plate, and 15 parts of ethylene glycol were added to the homogeneous solution to remove the diluent at 42° C. to obtain a polymer solution, and the polymer solution was cast into a film, i.e., a barrier layer. (4) A layer of solvent-based adhesive ethylene-vinyl acetate copolymer is coated on the matte layer, the water-blocking layer and the barrier layer respectively, and the matte layer, the water-blocking layer and the barrier layer are laminated and dried, and then a drying layer is added, and laminated under a hot pressing state of 100°C and 0.16MPa, and then a heat sealing layer is flatly attached, and after heating to 200°C, it is extruded and inflated with compressed air to obtain a packaging bag for functional food.

[0059] The preparation method of vitamin C chewable tablets comprises the following steps: L-ascorbic acid, sodium ascorbate, sorbitol, sucralose, aspartame, edible flavor, pigment and magnesium stearate were sieved through a 40-mesh sieve respectively. L-ascorbic acid, sodium ascorbate, sorbitol, sucralose, aspartame, edible flavor, pigment and magnesium stearate were weighed according to a weight ratio of 1.3:1.0:9.3:0.01:0.028:0.22:0.0025:0.14. Sorbitol, sucralose, aspartame, pigment and edible flavor were premixed in equal amounts and then sieved with L-ascorbic acid, sodium ascorbate and magnesium stearate. The materials are transported to a mixer through a closed pipeline filled with 99.999% nitrogen and mixed for 30 minutes. The materials after uniform mixing are transported to a rotary tablet press through a closed pipeline filled with 99.999% nitrogen. The materials are compressed under completely closed conditions filled with 99.999% nitrogen. The tablets obtained after compression are transported to the packaging process through a closed pipeline filled with 99.999% nitrogen. In the packaging process, tablets are first added to the packaging bag for functional foods and then filled with 99.999% nitrogen. Finally, the packaging bag is heat-sealed to obtain a vitamin C chewable tablet product.

[0060] Comparative Example 1 The structure and preparation method of the packaging bag are the same as those in Example 1.

[0061] The preparation method of vitamin C chewable tablets comprises the following steps: L-ascorbic acid, sodium ascorbate, sorbitol, sucralose, aspartame, edible flavor, pigment and magnesium stearate were sieved through a 40-mesh sieve respectively. L-ascorbic acid, sodium ascorbate, sorbitol, sucralose, aspartame, edible flavor, pigment and magnesium stearate were weighed according to a weight ratio of 1.3:1.0:9.3:0.01:0.028:0.22:0.0025:0.14. Sorbitol, sucralose Sugar, aspartame, pigment and edible flavor are premixed in equal amounts and then conveyed to a mixer with L-ascorbic acid, sodium ascorbate and magnesium stearate for mixing for 30 minutes. The evenly mixed materials are conveyed to a rotary tablet press for tableting. The tablets obtained after tableting are conveyed to a packaging process. In the packaging process, tablets are first added to the packaging bag and then filled with nitrogen with a purity of 99.999%. Finally, the packaging bag is heat-sealed to obtain a vitamin C chewable tablet product.

[0062] Comparative Example 2 There is no barrier layer in the structure of the packaging bag, and the other steps are the same as in Example 1.

[0063] Comparative Example 3 There is no drying layer in the structure of the packaging bag, and the other steps are the same as in Example 1.

[0064] Comparative Example 4 The packaging bag has no matte layer and drying layer, and the other steps are the same as in Example 1.

[0065] Effect verification: The gas permeability, water vapor permeability, light transmittance and nitrogen content in the packaging bags prepared in Example 1 and Comparative Examples 3-4 were evaluated respectively. At the same time, the sensory indicators of the vitamin C chewable tablets, namely, oral evaluation and external observation evaluation, were evaluated. The stability experiment of the vitamin C chewable tablets was divided into an accelerated stability experiment and a shelf life stability experiment.

[0066] The gas permeability is determined by the differential pressure method of GB / T 1038.1, the water vapor permeability is determined by the electrolytic sensor method of GB / T 21529, the light transmittance is determined by method A in GB / T 2410, the nitrogen content in the packaging bag is determined by reference to the "Sensor Method for Determination of Headspace Gas Content in Food Plastic Packaging Containers", and the taste and flavor evaluation is determined by electronic tongue.

[0067] In Comparative Example 2, since there is no barrier layer, the gas permeability of the packaging bag is too high, so there is no need to test the gas permeability, water vapor permeability and light transmittance of Comparative Example 2.

[0068] 1. Gas permeability, water vapor permeability and light transmittance testing The packaging bags prepared in Example 1 and Comparative Examples 3-4 were taken and their gas permeability, water vapor permeability and light transmittance were measured after being stored under the same temperature and humidity conditions for 24 hours. The results are shown in Table 1.

[0069]

[0070] The packaging bags prepared in Example 1 and Comparative Examples 3-4 were placed in a stability test box. The experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. An accelerated stability test was conducted for 3 months. The gas permeability, water vapor permeability and light transmittance were tested at 1, 2 and 3 months, respectively. The test results are shown in Tables 2-4.

[0071]

[0072]

[0073]

[0074] It can be seen from the data in Tables 2-4 that the gas permeability, water vapor permeability and light transmittance (light source wavelength 200-260 mm) of Example 1 during the acceleration process changed slightly, and were significantly better than those of Comparative Examples 3-4.

[0075] 2. Taste evaluation The products obtained in Example 1 and Comparative Examples 1-4 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by electronic tongue detection numerical results, taking sweet, sour, bitter, salty, fresh, astringent and other tastes as indicators. The products obtained in Example 1 and Comparative Examples 1-4 were placed in a stability test box, and the experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. The initial taste of the products and the taste of the products accelerated for 1, 2, and 3 months were evaluated respectively. After the test was completed, the statistical data were collected, and the results are shown in Tables 5, 6, 7, and 8.

[0076]

[0077]

[0078]

[0079]

[0080] From the values ​​of the product taste evaluation in Tables 5-8, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 1 during the acceleration process are very stable throughout the acceleration process, which is significantly better than that of Comparative Examples 1-4.

[0081] 3. External observation and evaluation The products in Example 1 and Comparative Examples 1-4 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test (0 months of acceleration), 1 month of acceleration, 2 months of acceleration, and 3 months of acceleration. The results of the changes in product appearance are shown in Table 1. Figure 1 .

[0082] from Figure 1 It can be seen that the appearance of the product of Example 1 did not change significantly during the accelerated process, while the appearance of the products of Comparative Examples 1-4 became significantly darker in color after 3 months of accelerated treatment, and obvious spots appeared on the surface, which did not meet the technical requirements for product appearance.

[0083] 4. Stability verification experiment The products in Example 1 and Comparative Examples 1-4 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test (accelerated for 0 months), 1 month, 2 months, and 3 months, respectively, to test various indicators. The results are shown in Tables 9, 10, 11, 12, 13, Figure 2 , Figure 3 and Figure 4 .

[0084]

[0085]

[0086]

[0087]

[0088]

[0089] From Table 9-13 and Figure 2-4 It can be seen that the moisture content, vitamin C content and nitrogen content in the package of the product of Example 1 did not change significantly during the acceleration process, while the nitrogen content in the package of the products of Comparative Examples 1-4 decreased significantly after 3 months of acceleration, the moisture content increased significantly, and the vitamin C attenuation obviously did not meet the requirements.

[0090] 5. Shelf life verification experiment The products in Example 1 and Comparative Examples 1-4 were subjected to shelf life verification tests. The products were stored at room temperature and the verification period was 24 months. During the shelf life, samples were taken once for 0 months, 3 months, 6 months, 12 months and 24 months, and various indicators were tested. The results are shown in Tables 14, 15, 16, 17, 18, Figure 5 , Figure 6 and Figure 7 .

[0091]

[0092]

[0093]

[0094]

[0095]

[0096] From Table 14-18 and Figure 5-7 It can be seen that the moisture content, vitamin C content and nitrogen content in the package of the product of Example 1 did not change significantly during the shelf storage period, while the nitrogen content in the package of the products of Comparative Examples 1-4 decreased significantly after 24 months of shelf storage, the moisture content increased significantly, and the vitamin C decayed significantly and did not meet the requirements.

[0097] 6. Palate evaluation during shelf life The products obtained in Example 1 and Comparative Examples 1-4 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by the electronic tongue detection numerical results using different tastes such as sweet, sour, bitter, salty, fresh, and astringent as indicators. The products obtained in Example 1 and Comparative Examples 1-4 were stored at room temperature. The initial taste of the products and the taste of the products stored at room temperature for 3, 6, 12, and 24 months were evaluated respectively. After the test was completed, the statistical data was collected. The results are shown in Tables 19, 20, 21, and 22.

[0098]

[0099]

[0100]

[0101]

[0102] From the values ​​of the product taste evaluation in Tables 19-22, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 1 during the shelf storage period are very stable throughout the accelerated process, which is significantly better than that of Comparative Examples 1-4.

[0103] 7. Verification of antioxidant properties of products with a shelf life of 24 months (1) Verify the protective effect of the product on H2O2-induced oxidative stress damage in L929 cells The survival rate of L929 cells after treatment with different concentrations of H2O2 is shown in the figure Figure 8 . Figure 8 The results showed that the survival rate of L929 cells gradually decreased with the increase of hydrogen peroxide concentration. When the H2O2 concentration increased to 500 μM, the survival rate of L929 cells was only 27.4%, indicating that severe oxidative stress damage occurred after H2O2 acted on L929 cells, indicating that the model was successfully established. The next step of the experiment was carried out using 200 μM H2O2 to determine the protective effect of the products prepared in Example 1 and Comparative Examples 1-4 on 200 μM H2O2-induced oxidative stress damage of L929 cells. L929 cells were cultured at 1×10 5The cells were inoculated at a density of 100 / well on a 96-well plate. After culturing for 24 hours, each 3 wells were grouped into a blank group, a damaged group, Example 1 group, Comparative Example 1 group, Comparative Example 2 group, Comparative Example 3 group and Comparative Example 4 group were set up respectively. 200 μL of culture medium containing the vitamin C chewable tablets obtained by removing the packaging of the products prepared in Example 1 and Comparative Examples 1-4 groups was added respectively (each product was added to 3 wells for parallel test, and the maximum safe concentration of the tested product was selected for test). 200 μL of culture medium without serum was added to the blank group and the damaged group for 24 hours. Except for the blank group, the supernatant was discarded from each well and H2O2 with a concentration of 200 μmol / L was added to induce damage. After 2 hours of action, the supernatant was discarded and 100 μL of MTT (0.5 mg / mL) solution was added. After culturing for 4 hours, the MTT solution was discarded and 150 μL of The DMSO solution dissolves the formazan produced by the living cells. After standing for 15 minutes, the absorbance value at 570 nm is measured with an ELISA instrument. The protective effect of the vitamin C chewable tablets obtained by removing the packaging of the products prepared in Example 1 and Comparative Examples 1-4 on the oxidative stress damage of L929 cells induced by 200 μM H2O2 was evaluated by cell viability. The survival rate of L929 cells treated with 200 μM H2O2 and the products stored for 24 months is shown in the figure. Fig. 9 .from Fig. 9 It can be seen that after the product of Example 1 acts on damaged cells, the cell survival rate is higher than that of the damaged group and Comparative Examples 1-4, and the protective effect of the product of Example 1 on oxidative stress damage caused by H2O2 is significantly stronger than that of Comparative Examples 1-4.

[0104] (2) Verify the level of active oxygen in cells after the product is applied Laser confocal microscopy was used to measure the inhibitory effect of the product on intracellular ROS production. The cell treatment was similar to the above method. After the cells were treated with H2O2, the culture medium was removed and the cells were washed three times with pre-cooled PBS. Then, they were stained with 6mM DCFH-DA at 37°C in the dark for 30 minutes, and the production of intracellular ROS was recorded using a laser confocal microscope.

[0105] The laser confocal microscopy results of the cells after the product was stored for 24 months are shown in the figure. Fig.10 The laser confocal microscopy results showed similar results, with strong green fluorescence in the blank group, indicating that a large amount of ROS existed in the cells. After 24 months of storage, the green fluorescence in L929 cells weakened after the products prepared in Example 1 and Comparative Examples 1-4 were used, indicating that ROS in L929 cells gradually decreased, and the level of ROS production in cells was reduced to varying degrees. The antioxidant capacity of the product in Example 1 was significantly stronger than that of Comparative Examples 1-4.

[0106] Example 2 The structure of the packaging bag for functional food is the same as that of Example 1.

[0107] A method for preparing a packaging bag for functional food comprises the following steps: (1) Matting layer preparation method 82 parts of polyamide, 15 parts of poly-4-methyl-1-pentene, 4 parts of polycarbonate fiber, 0.5 parts of vinyl triethoxysilane, 0.9 parts of vinyl tri(β-methoxyethoxy)silane, 2 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 1 part of 2,6-di-tert-butyl-p-cresol are fully mixed and fully melted and blended at 240° C. through a twin-screw extruder, extruded at 200° C., the melt is extruded into a thick sheet, and a sheet is cast at 35° C., and then longitudinally stretched 4 times at 146° C. and transversely stretched 8.5 times at 178° C., and the film is washed and dried after biaxial stretching, and cut to form a matte layer; (2) Preparation method of water-blocking layer: The polyvinyl alcohol masterbatch and the aluminum filler are mixed at a weight ratio of 94.5:5.5 in a closed mixing tank at 3°C ​​for 20 minutes to obtain a mixed material; the mixed material and oleic acid amide are added into a conical twin-screw roller extruder for extrusion, and the weight ratio of the polyvinyl alcohol masterbatch to the oleic acid amide is 94.5:7 to obtain a water-blocking layer; wherein the extrusion is extruded in a segmented temperature control manner, the melting section temperature is set to 78±2°C, the final melting homogenization section temperature is set to 92±2°C, the homogenization dispersion section temperature is set to 97±2°C, and the dispersion section temperature is set to 108±2°C; (3) Preparation method of barrier layer: 0.66 parts of fatty alcohol polyoxyethylene ether, 0.24 parts of ammonium persulfate solution with a mass concentration of 15%, 15 parts of ethylene and 0.8 parts of trifluorochloroethylene were added to 62 parts of deoxygenated deionized water, and the mixture was stirred and reacted at 70° C. for 6 hours to obtain a trifluorochloroethylene and ethylene (ECTFE) copolymer solution. 45 parts of diluent diethyl sebacate were added to the trifluorochloroethylene and ethylene copolymer solution, and the mixture was mixed at 200° C. to form a homogeneous solution. The homogeneous solution was poured on a glass plate, and 30 parts of ethylene glycol were added to the homogeneous solution to remove the diluent at 30° C. to obtain a polymer solution. The polymer solution was cast into a thin film, i.e., a barrier layer. (4) A layer of solvent-based adhesive ethylene-vinyl acetate copolymer is coated on the matte layer, the water-blocking layer and the barrier layer respectively, and the matte layer, the water-blocking layer and the barrier layer are laminated and dried, and then a drying layer is added, and laminated under a hot pressing state of 130°C and 0.21MPa, and then a heat sealing layer is flatly attached, and after heating to 195°C, it is extruded and inflated with compressed air to obtain a packaging bag for functional food.

[0108] The preparation method of a plurality of B vitamin bubble lozenges comprises the following steps: Vitamin B1, Vitamin B2, Vitamin B6, Vitamin B 12 , niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclamate, aspartame, sucralose and edible flavors were sieved through 80 mesh respectively, vitamin B1, vitamin B2, vitamin B6, vitamin B 12 , niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclohexylaminosulfonate, aspartame, sucralose and edible flavors are weighed according to the mass ratio of 1.49:1.32:1.582:0.00125:5.36:0.191:0.212:4.853:225.9:80:80:80:5.18:4.0:3.25:1.25:0.15:5.25, vitamin B1, vitamin B2, vitamin B6, D-calcium pantothenate, niacinamide, folic acid, D-biotin, vitamin B 12 The granulated materials, citric acid and lactose, were respectively premixed with sorbitol in equal amounts and in increasing steps. The granulated materials, citric acid and lactose, were transported to a wet granulator through a closed pipe filled with nitrogen gas with a purity of 99.999%. Purified water with a weight percentage of 8 wt.% was added to the granulated materials as a binder for granulation. After the granulation was completed, the obtained granules were transported to a high-efficiency boiling dryer through a closed pipe filled with nitrogen gas with a purity of 99.999%. The granules were dried at a drying temperature of 50±5°C for 25 minutes. After the materials were dried to a moisture content of 0.8-1.2%, they were passed through a closed pipe filled with nitrogen gas with a purity of 99.999% together with other materials. The materials are transported to a mixer through a closed pipe and mixed for 40 minutes. The evenly mixed materials are transported to a rotary tablet press through a closed pipe filled with nitrogen with a purity of 99.999%. Tablets are pressed under completely closed conditions with nitrogen filled with a purity of 99.999%. The tablets obtained after tableting are transported to the packaging process through a closed pipe filled with nitrogen with a purity of 99.999%. In the packaging process, tablets are first added to the packaging bag for functional foods and then filled with nitrogen with a purity of 99.999%. Finally, the packaging bag is heat-sealed to obtain bubble lozenges of various B vitamins.

[0109] Comparative Example 5 The structure and preparation method of the packaging bag are the same as those in Example 2.

[0110] The preparation method of a plurality of B vitamin bubble lozenges comprises the following steps: Vitamin B1, Vitamin B2, Vitamin B6, Vitamin B 12, niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclamate, aspartame, sucralose and edible flavors were sieved through 80 mesh respectively, vitamin B1, vitamin B2, vitamin B6, vitamin B 12 , niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclohexylaminosulfonate, aspartame, sucralose and edible flavors are weighed according to the mass ratio of 1.49:1.32:1.582:0.00125:5.36:0.191:0.212:4.853:225.9:80:80:80:5.18:4.0:3.25:1.25:0.15:5.25, vitamin B1, vitamin B2, vitamin B6, D-calcium pantothenate, niacinamide, folic acid, D-biotin, vitamin B 12 The granulated materials, citric acid and lactose, are respectively premixed with sorbitol in equal amounts and in increasing steps. The granulated materials, citric acid and lactose, are conveyed to a wet granulator. Purified water, which accounts for 8 wt.% of the granulated materials, is added as a binder for granulation. After the granulation is completed, the obtained granules are conveyed to a high-efficiency boiling dryer and dried at a drying temperature of 50±5°C for 25 minutes. After the materials are dried to a moisture content of 0.8-1.2%, they are conveyed to a mixer together with other materials and mixed for 40 minutes. The uniformly mixed materials are conveyed to a rotary tablet press for tableting. The tablets obtained after tableting are conveyed to a packaging process. In the packaging process, tablets are first added to the packaging bag and then filled with nitrogen with a purity of 99.999%. Finally, the packaging bag is heat-sealed to obtain a variety of B vitamin bubble lozenges.

[0111] Comparative Example 6 The structure and preparation method of the packaging bag are the same as those in Example 2.

[0112] The preparation method of a plurality of B vitamin bubble lozenges comprises the following steps: Vitamin B1, Vitamin B2, Vitamin B6, Vitamin B 12 , niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclamate, aspartame, sucralose and edible flavors were sieved through 80 mesh respectively, vitamin B1, vitamin B2, vitamin B6, vitamin B 12, niacinamide, folic acid, D-biotin, D-calcium pantothenate, sorbitol, citric acid, lactose, sodium bicarbonate, maltodextrin, magnesium stearate, sodium cyclohexylaminosulfonate, aspartame, sucralose and edible flavors are weighed according to the mass ratio of 1.49:1.32:1.582:0.00125:5.36:0.191:0.212:4.853:225.9:80:80:80:5.18:4.0:3.25:1.25:0.15:5.25, vitamin B1, vitamin B2, vitamin B6, D-calcium pantothenate, niacinamide, folic acid, D-biotin, vitamin B 12 The granulated materials, citric acid and lactose, were respectively premixed with sorbitol in equal amounts and in increasing steps. The granulated materials, citric acid and lactose, were transported to a wet granulator through a closed pipe filled with 99.999% nitrogen. 8wt.% of purified water was added to the granulated materials as a binder for granulation. After the granulation was completed, the obtained granules were transported to a high-efficiency boiling dryer through a closed pipe filled with 99.999% nitrogen. The granules were dried at a drying temperature of 50±5°C for 25 minutes. After the materials were dried to a moisture content of 0.8-1.2%, they were transported together with other materials through a closed pipe filled with 99.999% nitrogen. The mixture was mixed in a mixer for 40 minutes. The uniformly mixed material was transported to a rotary tablet press through a closed pipe filled with 99.999% nitrogen. The tablets were compressed under completely closed conditions with 99.999% nitrogen. The tablets obtained after compression were transported to the packaging process through a closed pipe filled with 99.999% nitrogen. In the packaging process, tablets were first added to the packaging bag used for functional foods and then filled with a mixed gas of 99.999% nitrogen and compressed air (the volume ratio of the two was 1:1). Finally, the packaging bag was heat-sealed to obtain a variety of B vitamin bubble lozenges.

[0113] Comparative Example 7 There is no drying layer in the structure of the packaging bag, and the other steps are the same as those in Example 2.

[0114] Comparative Example 8 The packaging bag has no matte layer and drying layer, and the other steps are the same as those in Example 2.

[0115] Effect verification: The sensory indices of the multiple B vitamin bubble lozenges prepared in Example 2 and Comparative Examples 5-8 were evaluated respectively, namely oral evaluation and external observation evaluation; the stability experiment of the multiple B vitamin bubble lozenges was divided into an accelerated stability experiment and a shelf life stability experiment.

[0116] The gas permeability is determined by the differential pressure method of GB / T 1038.1, the water vapor permeability is determined by the electrolytic sensor method of GB / T 21529, the light transmittance is determined by method A in GB / T 2410, the nitrogen content in the packaging bag is determined by reference to the "Sensor Method for Determination of Headspace Gas Content in Food Plastic Packaging Containers", and the taste and flavor evaluation is determined by electronic tongue.

[0117] 1. Gas permeability, water vapor permeability and light transmittance testing The packaging bags prepared in Example 2 and Comparative Examples 7-8 were taken and their gas permeability, water vapor permeability and light transmittance were measured after being stored under the same temperature and humidity conditions for 24 hours. The results are shown in Table 23.

[0118]

[0119] The packaging bags prepared in Example 2 and Comparative Examples 7-8 were placed in a stability test box. The experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. An accelerated stability test was conducted for 3 months. The gas permeability, water vapor permeability and light transmittance were tested at 1, 2 and 3 months, respectively. The test results are shown in Tables 24-26.

[0120]

[0121]

[0122]

[0123] It can be seen from the data in Tables 23-26 that the gas permeability, water vapor permeability and light transmittance (light source wavelength 200-260 mm) of Example 2 changed little during the acceleration process, and were significantly better than those of Comparative Examples 7-8.

[0124] 2. Taste evaluation The products obtained in Example 2 and Comparative Examples 5-8 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by the electronic tongue detection numerical results, taking sweet, sour, bitter, salty, fresh, astringent and other different tastes as indicators. The products obtained in Example 2 and Comparative Examples 5-8 were placed in a stability test box, and the experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. The initial taste of the product was evaluated, and the taste of the product was accelerated for 1, 2, and 3 months, and the statistical data was collected after the test was completed. The results are shown in Tables 27-30.

[0125]

[0126]

[0127]

[0128]

[0129] From the values ​​of the product taste evaluation in Tables 27-30, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 2 during the acceleration process are very stable throughout the acceleration process, which is significantly better than that of Comparative Examples 5-8.

[0130] 3. External observation and evaluation The products obtained in Example 2 and Comparative Examples 5-8 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test (0 months of acceleration), 1 month of acceleration, 2 months of acceleration, and 3 months of acceleration. The results of the changes in product appearance are shown in Table 1. Fig.11 .

[0131] from Fig.11 It can be seen that the appearance of the product of Example 2 did not change significantly during the accelerated process, while the appearance of the products of Comparative Examples 5-8 became significantly darker in color after 3 months of acceleration, and obvious spots appeared on the surface, which did not meet the technical requirements for product appearance.

[0132] 4. Stability verification experiment The products prepared in Example 2 and Comparative Examples 5-8 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test, 1 month, 2 months, and 3 months, and various indicators were tested. The results are shown in Tables 31-35.

[0133]

[0134]

[0135]

[0136]

[0137]

[0138] It can be seen from Tables 31-35 that the moisture content, vitamin content and nitrogen content in the package of the product of Example 2 did not change significantly during the accelerated process, while the nitrogen content in the package of the products of Comparative Examples 5-8 decreased significantly after 3 months of acceleration, the moisture content increased significantly, the vitamin content attenuated significantly, and some ingredients that did not meet the requirements appeared.

[0139] 5. Shelf life verification experiment The products prepared in Example 2 and Comparative Examples 5-8 were subjected to shelf life verification tests. The products were stored at room temperature and the verification period was 24 months. During the shelf life storage period, samples were taken once for 0 months, 3 months, 6 months, 12 months and 24 months, and various indicators were tested. The results are shown in Tables 36-40.

[0140]

[0141]

[0142]

[0143]

[0144]

[0145] As can be seen from Tables 36-40, the moisture content, the content of each component of B vitamins and the nitrogen content in the package of the product of Example 2 did not change significantly during the shelf storage period, while the nitrogen content in the package of the products of Comparative Examples 5-8 decreased significantly, their moisture content increased significantly, and the components of B vitamins attenuated to varying degrees after 24 months of shelf storage, which no longer met the requirements.

[0146] 6. Shelf life taste evaluation The products prepared in Example 2 and Comparative Examples 5-8 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by the electronic tongue detection numerical results using different tastes such as sweet, sour, bitter, salty, fresh, and astringent as indicators. The products prepared in Example 2 and Comparative Examples 5-8 were stored at room temperature, and the initial taste of the products and the taste of the products stored at room temperature for 3, 6, 12, and 24 months were evaluated. After the test was completed, the statistical data were collected, and the results are shown in Tables 41-44.

[0147]

[0148]

[0149]

[0150]

[0151] From the values ​​of the product taste evaluation in Tables 41-44, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 2 during the acceleration process are very stable throughout the acceleration process, which is significantly better than that of Comparative Examples 5-8.

[0152] Example 3 The structure of the packaging bag for functional food is the same as that of Example 1.

[0153] A method for preparing a packaging bag for functional food comprises the following steps: (1) Matting layer preparation method 80 parts of polyamide, 8 parts of poly-4-methyl-1-pentene, 7 parts of polycarbonate fiber, 1.5 parts of vinyl triethoxysilane, 0.8 parts of vinyl tri(β-methoxyethoxy)silane, 1.1 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.8 parts of 2,6-di-tert-butyl-p-cresol are fully mixed and fully melted and blended at 310° C. through a twin-screw extruder, extruded at 230° C., the melt is extruded into a thick sheet, and a sheet is cast at 30° C., and then longitudinally stretched 6 times at 135° C. and transversely stretched 7.9 times at 165° C., and the film is washed and dried after biaxial stretching, and cut to form a matte layer; (2) Preparation method of water-blocking layer: The polyvinyl alcohol masterbatch and the aluminum filler are mixed at a weight ratio of 96:3.5 in a closed mixing tank at 12°C for 25 minutes to obtain a mixed material; the mixed material and oleic acid amide are added into a conical twin-screw roller extruder for extrusion, and the weight ratio of the polyvinyl alcohol masterbatch to the oleic acid amide is 96:2.5 to obtain a water-blocking layer; wherein the extrusion is extruded in a segmented temperature control manner, the melting section temperature is set to 82±2°C, the final melting homogenization section temperature is set to 92±2°C, the homogenization dispersion section temperature is set to 98±2°C, and the dispersion section temperature is set to 110±2°C; (3) Preparation method of barrier layer: 1.25 parts of fatty alcohol polyoxyethylene ether, 0.6 parts of ammonium persulfate solution with a mass concentration of 13%, 28 parts of ethylene and 1.1 parts of trifluorochloroethylene were added to 70 parts of deoxygenated deionized water, and the mixture was stirred and reacted at 105° C. for 8 hours to obtain a trifluorochloroethylene and ethylene (ECTFE) copolymer solution, 53 parts of diluent diethyl sebacate were added to the trifluorochloroethylene and ethylene copolymer solution, and the mixture was mixed at 235° C. to form a homogeneous solution, and the homogeneous solution was poured on a glass plate, 37 parts of ethylene glycol were added to the homogeneous solution, and the diluent was removed at 50° C. to obtain a polymer solution, and the polymer solution was cast into a film, i.e., a barrier layer; (4) A layer of solvent-based adhesive ethylene-vinyl acetate copolymer is coated on the matte layer, the water-blocking layer and the barrier layer respectively, and the matte layer, the water-blocking layer and the barrier layer are laminated and dried, and then a drying layer is added, and laminated under a hot pressing state of 200°C and 0.41MPa, and then a heat sealing layer is flatly attached, and after heating to 210°C, it is extruded and inflated with compressed air to obtain a packaging bag for functional food.

[0154] The preparation method of calcium vitamin D chewable tablets comprises the following steps: Calcium carbonate, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are respectively sieved with a 60-mesh screen, and vitamin D3 is sieved with a 40-mesh screen. Calcium carbonate, vitamin D3, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are weighed according to a weight ratio of 3.5:0.006:1.94:1.05:0.28:0.14:0.0175:0.007. Vitamin D3, edible flavor and aspartame are premixed with part of whole milk powder in equal amounts and in increasing steps. The granulated materials calcium carbonate and microcrystalline cellulose are transported to a wet granulator through a closed pipeline filled with nitrogen with a purity of 99.999%, and an ethanol aqueous solution with a mass concentration of 20% and a total mass of 9wt.% of calcium carbonate and microcrystalline cellulose is added as a binder for granulation. After completion, the obtained granules are transported to a high-efficiency boiling dryer through a closed pipe filled with 99.999% nitrogen, and dried at a drying temperature of 60±5°C for 30 minutes. After the material is dried to a moisture content of 1.3-1.6%, it is transported to a mixer together with other materials through a closed pipe filled with 99.999% nitrogen and mixed for 30 minutes. The evenly mixed materials are transported to a rotary tablet press through a closed pipe filled with 99.999% nitrogen, and tablets are pressed under completely closed conditions filled with 99.999% nitrogen. The tablets obtained after tableting are transported to the packaging process through a closed pipe filled with 99.999% nitrogen. In the packaging process, tablets are first added to the packaging bag for functional foods and then filled with 99.999% nitrogen. Finally, the packaging bag is heat-sealed to obtain calcium vitamin D chewable tablets.

[0155] Comparative Example 9 The structure and preparation method of the packaging bag are the same as those in Example 3.

[0156] The preparation method of calcium vitamin D chewable tablets comprises the following steps: Calcium carbonate, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are sieved through 60 meshes respectively, vitamin D3 is sieved through 40 meshes, calcium carbonate, vitamin D3, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are weighed according to the weight ratio of 3.5:0.006:1.94:1.05:0.28:0.14:0.0175:0.007, vitamin D3, edible flavor and aspartame are premixed with part of whole milk powder in equal amounts, the granulation materials calcium carbonate and microcrystalline cellulose are transported to the wet granulator, and added A 20% ethanol aqueous solution with a mass concentration of 9 wt.% of the total mass of calcium carbonate and microcrystalline cellulose is used as a binder for granulation. After granulation, the obtained granules are conveyed to a high-efficiency boiling dryer and dried at a drying temperature of 60±5°C for 30 minutes. After the material is dried to a moisture content of 1.3-1.6%, it is conveyed to a mixer together with other materials for mixing for 30 minutes. The evenly mixed material is conveyed to a rotary tablet press for tableting. The tablets obtained after tableting are conveyed to a packaging process. In the packaging process, tablets are first added to the packaging bag and then filled with nitrogen with a purity of 99.999%. Finally, the packaging bag is heat-sealed to obtain calcium vitamin D chewable tablets.

[0157] Comparative Example 10 The structure and preparation method of the packaging bag are the same as those in Example 3.

[0158] The preparation method of calcium vitamin D chewable tablets comprises the following steps: Calcium carbonate, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are respectively sieved with a 60-mesh screen, and vitamin D3 is sieved with a 40-mesh screen. Calcium carbonate, vitamin D3, sorbitol, whole milk powder, microcrystalline cellulose, edible flavor, aspartame and magnesium stearate are weighed according to a weight ratio of 3.5:0.006:1.94:1.05:0.28:0.14:0.0175:0.007. Vitamin D3, edible flavor and aspartame are premixed with part of whole milk powder in equal amounts and in increasing steps. The granulated materials calcium carbonate and microcrystalline cellulose are transported to a wet granulator through a closed pipeline filled with nitrogen with a purity of 99.999%. An ethanol aqueous solution with a mass concentration of 20% and a total mass of 9wt.% of calcium carbonate and microcrystalline cellulose is added as a binder for granulation. After granulation, the obtained granules are The material is transported to a high-efficiency boiling dryer through a closed pipeline filled with 99.999% nitrogen, dried at a drying temperature of 60±5°C for 30 minutes, and after the material is dried to a moisture content of 1.3-1.6%, it is transported together with other materials to a mixer through a closed pipeline filled with 99.999% nitrogen and mixed for 30 minutes. The evenly mixed material is transported to a rotary tablet press through a closed pipeline filled with 99.999% nitrogen, and tableted under completely closed conditions filled with 99.999% nitrogen. The tablets obtained after tableting are transported to the packaging process through a closed pipeline filled with 99.999% nitrogen. In the packaging process, tablets are first added to the packaging bag and then filled with a mixed gas of 99.999% nitrogen and compressed air (the volume ratio of the two is 1:1). Finally, the packaging bag is heat-sealed to obtain calcium vitamin D chewable tablets.

[0159] Comparative Example 11 There is no drying layer in the structure of the packaging bag, and the other steps are the same as those in Example 3.

[0160] Comparative Example 12 The packaging bag does not have a matte layer and a drying layer, and the other steps are the same as those in Example 3.

[0161] Comparative Example 13 There is no water-blocking layer in the packaging bag structure, and the other steps are the same as those in Example 3.

[0162] Effect verification: The sensory indices of the calcium vitamin D chewable tablets prepared in Example 3 and Comparative Examples 9-12 were evaluated respectively, namely oral evaluation and external observation evaluation; the stability experiment of the calcium vitamin D chewable tablets was divided into an accelerated stability experiment and a shelf life stability experiment.

[0163] The gas permeability is determined by the differential pressure method of GB / T 1038.1, the water vapor permeability is determined by the electrolytic sensor method of GB / T 21529, the light transmittance is determined by method A in GB / T 2410, the nitrogen content in the packaging bag is determined by reference to the "Sensor Method for Determination of Headspace Gas Content in Food Plastic Packaging Containers", and the taste and flavor evaluation is determined by electronic tongue.

[0164] In Comparative Example 13, since there is no water-blocking layer, the water vapor permeability of the packaging bag is too high, so there is no need to conduct subsequent testing on Comparative Example 13.

[0165] 1. Gas permeability, water vapor permeability and light transmittance testing The packaging bags prepared in Example 3 and Comparative Examples 11-12 were taken and their gas permeability, water vapor permeability and light transmittance were measured after being stored under the same temperature and humidity conditions for 24 hours. The results are shown in Table 45.

[0166]

[0167] The packaging bags prepared in Example 3 and Comparative Examples 11-12 were placed in a stability test box. The experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. An accelerated stability test was conducted for 3 months. The gas permeability, water vapor permeability and light transmittance were tested at 1, 2 and 3 months, respectively. The test results are shown in Tables 46-48.

[0168]

[0169]

[0170]

[0171] It can be seen from the data in Tables 45-48 that the gas permeability, water vapor permeability and light transmittance (light source wavelength 200-260 mm) of Example 3 during the acceleration process changed little, and were significantly better than those of Comparative Examples 11-12.

[0172] 2. Taste evaluation The products obtained in Example 3 and Comparative Examples 9-12 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by the electronic tongue detection numerical results, taking sweet, sour, bitter, salty, fresh, astringent and other different tastes as indicators. The products obtained in Example 3 and Comparative Examples 9-12 were placed in a stability test box, and the experimental conditions were a temperature of 37°C ± 2°C and a relative humidity of 75% ± 5%. The initial taste of the product, and the taste of the product after 1, 2, and 3 months were evaluated respectively. After the test was completed, the statistical data were collected, and the results are shown in Tables 49-52.

[0173]

[0174]

[0175]

[0176]

[0177] From the values ​​of the product mouthfeel evaluation in Tables 49-52, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 3 during the acceleration process are very stable throughout the acceleration process, which is significantly better than that of Comparative Examples 9-12.

[0178] 3. External observation and evaluation The products obtained in Example 3 and Comparative Examples 9-12 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test (0 months of acceleration), 1 month of acceleration, 2 months of acceleration, and 3 months of acceleration. The results of the changes in product appearance are shown in Table 1. Fig.12 .

[0179] from Fig.12 It can be seen that the appearance of the product of Example 3 did not change significantly during the accelerated process, while the appearance of the products of Comparative Examples 9-12 became significantly darker in color after 3 months of acceleration, and obvious spots appeared on the surface, which did not meet the technical requirements for product appearance.

[0180] 4. Stability verification experiment The products prepared in Example 3 and Comparative Examples 9-12 were subjected to accelerated tests. The accelerated tests were conducted in a drug stability test chamber with a temperature setting of 37°C ± 2°C and a relative humidity of 75% ± 5%. The validation period was 3 months. During the validation period, samples were taken from the initial product before the accelerated test, 1 month, 2 months, and 3 months, and various indicators were tested. The results are shown in Tables 53-57.

[0181]

[0182]

[0183]

[0184]

[0185]

[0186] It can be seen from Tables 53-57 that the moisture content, vitamin content and nitrogen content in the package of the product of Example 3 did not change significantly during the accelerated process, while the nitrogen content in the package of the products of Comparative Examples 9-12 decreased significantly after 3 months of acceleration, their moisture content increased significantly, and the vitamin D3 component attenuated significantly and did not meet the product requirements.

[0187] 5. Shelf life verification experiment The products prepared in Example 3 and Comparative Examples 9-12 were subjected to shelf life verification tests. The products were stored at room temperature and the verification period was 24 months. During the shelf life storage period, samples were taken once for 0 months, 3 months, 6 months, 12 months and 24 months, and various indicators were tested. The results are shown in Tables 58-62.

[0188]

[0189]

[0190]

[0191]

[0192]

[0193] It can be seen from Tables 58-62 that the moisture content, the content of each nutrient component and the nitrogen content in the package of the product of Example 3 did not change significantly during the shelf storage period, while the nitrogen content in the package of the products of Comparative Examples 9-12 decreased significantly, their moisture content increased significantly, and the vitamin D3 content decreased to varying degrees after 24 months of shelf storage, which no longer met the product requirements.

[0194] 6. Palate evaluation during shelf life The products obtained in Example 3 and Comparative Examples 9-12 were evaluated for initial taste, and the taste of the evaluation carrier was evaluated by the electronic tongue detection numerical results, taking sweet, sour, bitter, salty, fresh, astringent and other tastes as indicators. The products obtained in Example 3 and Comparative Examples 9-12 were stored at room temperature, and the initial taste of the products and the taste of the products stored at room temperature for 3, 6, 12, and 24 months were evaluated. After the test was completed, the statistical data were collected, and the results are shown in Tables 63-66.

[0195]

[0196]

[0197]

[0198]

[0199] From the values ​​of the product taste evaluation in Tables 63-66, it can be seen that the sourness, sweetness, bitterness, saltiness, astringency, umami, bitter aftertaste, astringent aftertaste and richness of the product of Example 3 during the acceleration process are very stable throughout the acceleration process, which is significantly better than that of Comparative Examples 9-12.

Claims

1. A packaging bag for functional food, characterized in that It includes a matt layer, a water-blocking layer, a barrier layer, a drying layer and a heat-sealing layer, which are connected in sequence from top to bottom; the matt layer is made of polyamide, a matting agent, a coupling agent and an antioxidant, the water-blocking layer is made of polyvinyl alcohol masterbatch, a filler and a lubricant, the barrier layer is a film of a copolymer of ethylene and chlorotrifluoroethylene, the drying layer is a silica gel desiccant layer, and the heat-sealing layer is made of high-density polyethylene.

2. The packaging bag for functional food according to claim 1, characterized in that The matting agent is poly-4-methyl-1-pentene and polycarbonate fiber, the coupling agent is vinyl triethoxysilane and vinyl tri(β-methoxyethoxy) silane, and the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 2,6-di-tert-butyl-p-cresol.

3. The packaging bag for functional food according to claim 1, characterized in that The filler is aluminum, and the weight ratio of the polyvinyl alcohol masterbatch to the filler is 94.5-96:3.5-5.5; the lubricant is oleic acid amide, and the weight ratio of the polyvinyl alcohol masterbatch to the lubricant is 94.5-96:2.5-7.

4. A method for preparing a packaging bag for functional food according to any one of claims 1 to 3, characterized in that The steps include: (1) Preparation of matt layer The polyamide, matting agent, coupling agent and antioxidant are mixed evenly and added into a twin-screw extruder for melt blending, extrusion, chilling casting, biaxial stretching, washing, drying and cutting to obtain a matting layer; (2) Preparation of water-blocking layer: The polyvinyl alcohol masterbatch is mixed with the filler to obtain a mixed material; the mixed material and the lubricant are added into a conical twin-screw roller extruder and extruded to obtain a water-blocking layer; (3) Preparation of barrier layer: Add a surfactant, an initiator, ethylene and chlorotrifluoroethylene into deoxygenated deionized water, stir and react to obtain a copolymer solution of chlorotrifluoroethylene and ethylene, add a diluent into the copolymer solution of chlorotrifluoroethylene and ethylene to form a homogeneous solution, pour the homogeneous solution onto a glass plate, add an extractant into the homogeneous solution to remove the extractant, and obtain a polymer solution, and cast the polymer solution into a film, i.e., a barrier layer; (4) A layer of solvent-based adhesive is coated on the matte layer, the water-blocking layer and the barrier layer respectively, and the matte layer, the water-blocking layer and the barrier layer are laminated and dried, and then a drying layer is added for hot pressing and lamination, and then a heat sealing layer is flatly attached, extruded after heating, and inflated with compressed air to obtain a packaging bag for functional food.

5. The method for preparing a packaging bag for functional food according to claim 4, characterized in that In step (1), the melt blending temperature is 240-350°C, the extrusion temperature is 180-230°C, and the chilled casting temperature is 25-35°C.

6. The method for preparing a packaging bag for functional food according to claim 4, characterized in that In step (2), the mixing temperature is 3-12° C. and the mixing time is 15-25 min.

7. The method for preparing a packaging bag for functional food according to claim 4, characterized in that In step (3), the surfactant is one or both of fatty alcohol polyoxyethylene ether or polyoxypropylene ether phosphate, the initiator is an ammonium persulfate solution with a mass concentration of 10-15%, the stirring reaction temperature is 55-105°C, the stirring reaction time is 4.5-8 hours, the diluent is one of dimethyl phthalate, diethyl phthalate, diethyl sebacate, tricresyl phosphate or benzophenone, the mixing temperature is 175-235°C, the extractant is one of methanol, ethanol, propanol, n-butanol or ethylene glycol, the removal temperature is 30-50°C, and the mass ratio of deoxygenated deionized water, surfactant, initiator, ethylene, chlorotrifluoroethylene, diluent and extractant is 55-70: 0.12-1.25:0.08-0.6:15-28:0.8-1.2:25-53:15-37。 8. The method for preparing a packaging bag for functional food according to claim 4, characterized in that In step (4), the solvent-based adhesive is ethylene-vinyl acetate copolymer; the hot pressing compounding temperature is 100-200°C, the hot pressing compounding pressure is 0.16-0.41 MPa, and the heating temperature is 195-210°C.

9. A freshness-locking process for a functional food packaging bag according to any one of claims 1 to 3, characterized in that After the functional food raw materials are pre-treated and weighed, the raw materials are transported to a mixer through a closed pipe filled with inert gas for uniform mixing. The uniformly mixed raw materials are transported to a tableting process through a closed pipe filled with inert gas. Tablets are pressed under completely closed conditions filled with inert gas. The tablets obtained after tableting are transported to a packaging process through a closed pipe filled with inert gas. In the packaging process, tablets are first added to the packaging bag for functional food and then filled with inert gas. Finally, the packaging bag is heat-sealed to obtain a functional food product.

10. A freshness-locking process for a functional food packaging bag according to any one of claims 1 to 3, characterized in that After the raw materials of the functional food are pre-treated and weighed, the raw materials used for granulation in the raw materials are transported to the granulation process through a closed pipe filled with inert gas for granulation, the obtained granules are transported to the drying process through a closed pipe filled with inert gas for drying, the dried granules and the remaining raw materials are transported to a mixer through a closed pipe filled with inert gas for uniform mixing, the mixed materials are transported to the tableting process through a closed pipe filled with inert gas, tablets are pressed under completely closed conditions filled with inert gas, the tablets obtained after tableting are transported to the packaging process through a closed pipe filled with inert gas, tablets are first added to the packaging bag for the functional food in the packaging process, and then filled with inert gas, and finally the packaging bag is heat-sealed to obtain a functional food product.

Citation Information

Patent Citations

  • Temperature-sensitive color-changing plastic packaging film

    CN111688315A

  • Method for preparing ethylene-trifluorochlor oethylene copolymer porous membrane

    CN102228805A

  • Method for preparing chlorotrifluoroethylene-ethylene copolymer

    CN102585070A

  • Composite matting masterbatch for BOPA film and preparation technology thereof

    CN107868447A

  • Antibacterial matt nylon composite film and packaging bag

    CN219583718U